Effect of Knowledge Management Practices on Employee Performance: : A Study on Some Selected Private Commercial Banks in Bangladesh - Rubel, Md. (Jahangirnagar University Journal of Management Research, 2024)
In today’s world, knowledge management is a crucial factor that confirms the success and sustainability of any organization. The prime goal of this study is to examine the effect of knowledge management practices on employee performance inside the private commercial banks in Bangladesh. The research utilized both primary and secondary data sources. For collecting primary data, a five-point Likert scale structured questionnaire was used. All the participants of the study were the employees of the twelve (12) selected private commercial banks located in Dhaka City, Bangladesh. The sample size was 146. The secondary data has been collected from different knowledge management books, several journal articles, the Internet, and various bank documents. Survey data were summarized using percentages, frequencies, means, and standard deviations. Regression analysis is employed while making inferences and assessing hypotheses. After analyzing the data, the study concluded that there is a positive relationship between knowledge management practices and employee performance. For this reason, to enhance employee performance, banking organizations should focus on knowledge management practices.